Gender differences related to the health and lifestyle patterns of university students - Christine Janse van Rensburg; Jhalukpreya Surujlal (AOSIS, 2013)
One of the transitions from adolescence to adulthood is the admission of students to a university setting. Accompanying this transition is a new-found independence which results in university students having more autonomy over their lifestyles and behaviours. The assumption in this setting is that many students are likely to engage in unhealthy and risky lifestyle behaviours which include alcohol abuse, tobacco use, physical inactivity and unhealthy dietary practices which may adversely affect their health in the long-term. In South Africa, research with regard to health and lifestyle patterns amongst both male and female young adults remains limited. The purpose of this study was, therefore, to investigate whether male and female students differed in relation to their health and lifestyles, as well as the related consequences thereof. A convenience sampling technique was used, where questionnaires were administered to 400 students at three university campuses in the Gauteng province of South Africa. An exploratory data analysis for health factors was used in order to retrieve relevant factors from a factor and regression analysis. Differences in gender were tested by using cross-tabulation for descriptive statistics and Chi-square analysis. The study found no statistically-significant differences between genders relating to the three emerging health factors, namely Gastrointestinal, Upper Respiratory Infections and Total Health Problems. However, descriptive statistics of lifestyle habits revealed that more female students exercised, smoked and binged on food than their male counterparts. It was also found that female students reported a higher incidence of stress than male students. It was concluded that university students do indeed engage in behaviours and lifestyles that place them at risk for serious health problems. In die oorgang van adolessensie na jong volwassene, bevind studente hulself binne 'n universiteitsomgewing. Gepaartgaande met hierdie oorgang word nuutgevonde vryheid verkry, wat veroorsaak dat universiteitstudente meer beheer oor hul lewenstyl en gedrag uitoefen. Die waarskynlikheid bestaan dat baie studente in hierdie omgewing betrokke sal raak by 'n ongesonde en gewaagde lewenstyl, wat alkohol misbruik, tabak gebruik, fisieke onaktiwiteit en ongesonde eetgewoontes insluit. Bogenoemde is faktore wat student se gesondheid oor die langtermyn nadelig sal beïnvloed. Navorsing in Suid-Afrika oor gesondheid en lewenstylpatrone van verskillende geslagsgroepe onder jong volwassenes is skaars. Die doel van hierdie studie was dus om ondersoek in te stel aangaande geslagsverskille in gesondheid en lewenstyl van studente, asook die betrokke nagevolge daarvan. 'n Gerieflikheids-steekproeftegniek is gebruik waartydens 400 vraelyste aan studente by drie verskillende universiteitskampusse in die Gauteng provinsie in Suid-Afrika versprei is. 'n Ondersoekende data analiese vir gesondheidsfakore is gebruik om toepaslike faktore te verkry vanuit 'n faktor- en regressie analiese. Geslagsverskille is getoets deur gebruik te maak van kruis-tabulering vir beskrywende statistiek asook 'n 'Chi-square' analiese. Die studie het geen statisties-betekenisvolle verskille tussen geslagte getoon ten opsigte van die drie gesondheidsfaktore naamlik Gastro-intestinale, Boonste Asemhalingstelsel en Totale Gesondheid Probleme nie. Nietemin het beskrywende statistiek ten opsigte van lewenstyl gewoontes egter onthul dat meer vroulike studente aan fisieke aktiwiteit delneem, rook en hul vergryp aan kos. Daar is ook gevind dat vroulike studente meer gevalle van spanning gerapporteer het as manlike studente. Die gevolgtrekking is dus dat universiteitstudente wel betrokke raak by gedrag en lewenstyle wat hul in gevaar stel vir ernstige gesondheidsprobleme.